2008
DOI: 10.1111/j.1365-2958.2008.06426.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk suppression between the CpxA–CpxR and EnvZ–OmpR two‐component systems in E. coli

Abstract: SummaryMany bacteria possess large numbers of twocomponent signalling systems, which are composed of histidine kinase-response regulator pairs. The high level of sequence similarity between some systems raises the possibility of undesired cross-talk between a histidine kinase and a non-cognate response regulator. Although molecular specificity ensures that phospho-transfer occurs primarily between correct partners, even a low level of inappropriate cross-talk could lead to unacceptable levels of noise or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
145
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 64 publications
(98 reference statements)
5
145
1
1
Order By: Relevance
“…Intensive experimental study over the past 10 years has revealed the biochemical and biophysical basis for this lack of promiscuity. In general, HKs demonstrate a strong "kinetic preference" for their cognate substrates, preferentially phosphorylating them on short timescales (7,15,16,(18)(19)(20)(21). A relatively small number of residues in the protein-protein interaction interface between HKs and RRs is responsible for maintaining this specificity (14)(15)(16)(20)(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive experimental study over the past 10 years has revealed the biochemical and biophysical basis for this lack of promiscuity. In general, HKs demonstrate a strong "kinetic preference" for their cognate substrates, preferentially phosphorylating them on short timescales (7,15,16,(18)(19)(20)(21). A relatively small number of residues in the protein-protein interaction interface between HKs and RRs is responsible for maintaining this specificity (14)(15)(16)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Bacterial TCS networks show a remarkably different topology: HKs usually act on a single target (12)(13)(14)(15)(16)(17). Intensive experimental study over the past 10 years has revealed the biochemical and biophysical basis for this lack of promiscuity.…”
mentioning
confidence: 99%
“…Many response regulators can be nonspecifically phosphorylated by the cellular pool of acetylphosphate [18][19][20]; by acting as phosphatases for their cognate response regulators, histidine kinases effectively clear this spurious, signal-independent phosphorylation [21]. Consequently, mutations that eliminate the phosphatase activity of a histidine kinase, including deletion of the histidine kinase gene, can lead to the inappropriate activation of the kinase's cognate response regulator under non-inducing conditions (Fig.…”
Section: Mechanisms Ensuring Specificity In Two-component Signaling Pmentioning
confidence: 99%
“…Consequently, mutations that eliminate the phosphatase activity of a histidine kinase, including deletion of the histidine kinase gene, can lead to the inappropriate activation of the kinase's cognate response regulator under non-inducing conditions (Fig. 2a) [21].…”
Section: Mechanisms Ensuring Specificity In Two-component Signaling Pmentioning
confidence: 99%
See 1 more Smart Citation